Gojek's Strategy to Win the Online Transportation Competition - Diah Ernawati; Hilman Lutfi (Jurnal Manajemen Bisnis, 2022)
Research aims: This research aimed to design an effective approach in competing in the digital era, especially in the transportation sector. The approach in question begins with determining specific targets to be achieved, namely identifying Gojek's strengths, weaknesses, opportunities, and threats associated with Grab as its business competition in Indonesia and the targeted market abroad. Design/Methodology/Approach: This research used Pearson Analysis, Porter’s Five Forces and SWOT analysis, using survey data that can describe the decision-making of transportation services (decision tree) to create a TOWS matrix describing Gojek's current internal and external conditions. Research findings: The results revealed that the right bottom-up approach would make it easier for Gojek to address socio-cultural issues in Indonesia. The aspect of ease of use of online applications on Gojek becomes capital influencing good socio-cultural acceptability, and service approaches in the form of tariffs, timeliness of pick-up, and driver cleanliness affect ride-sharing options.Theoretical contribution/Originality: This study examines the use of the right bottom-up approach that will make it easier for Gojek to address socio-cultural issues in Indonesia.Practitioner/Policy implication: Service approaches in the form of tariffs, timeliness of pick-up, and driver cleanliness become a priority of ride-sharing customers.Research limitation/Implication: This research was only conducted in DKI Jakarta, West Java, and Banten.